Peru : 2019 Article IV Consultation-Press Release; Staff Report; Staff Statement and Statement by the Executive Director for Peru. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation discusses that Peru's economic performance continues to be strong, however, external and domestic headwinds, including the fallout from Lava Jato corruption investigations, have reduced growth momentum and raised concerns about long-term growth prospects. Policy responses have been appropriate, but further reforms have been delayed by a political stalemate between the executive and legislative powers. After President Vizcarra dissolved Congress in September 2019, new parliamentary elections will be held in January 2020. The current slowdown in activity and heightened uncertainty justify policy stimulus. However, the fiscal stance is procyclical owing to higher-than-expected revenues and low execution of public investment. Against this background, monetary policy easing is particularly appropriate given the absence of inflationary pressures, while accelerated budget execution would mitigate the procyclical fiscal policy stance. In the medium term, additional fiscal space from tax revenues and effective expenditure control is needed to address priorities in infrastructure and social spending while a gradual transition to greater exchange rate flexibility would foster financial market development. In addition to infrastructure investment, key reforms are needed to improve governance and fight corruption, boost competitiveness, and reduce informality.